2006
DOI: 10.1002/app.25488
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and optimization of 2,4‐D loaded cellulose derivatives microspheres by solvent evaporation technique

Abstract: Controlled release herbicide formulations were prepared by microencapsulation using solvent evaporation technique. 2,4-D was chosen as core material, which was microencapsulated in two cellulose derivatives as matrices: cellulose acetate butyrate butyryl (CAB) and ethylcellulose (EC). The work is intended to produce systems containing the herbicide to reduce its risks by dermal contact, evaporation, or degradation and to control the release of the active agent. The microspheres loaded by 2,4-D were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…1): the emulsification of a polymer solution containing the encapsulated substance, followed by particle hardening through solvent evaporation and polymer precipitation. During the water emulsification, the polymer in solution in the volatile, waterimmiscible solvent is broken into microdroplets by the shear stress produced by either a homogenizer or a sonicator in the presence of a surface-active agent until the polymer precipitates [24][25][26][27].…”
Section: Preparation Of Pei Dispersions By Emulsion/evaporationmentioning
confidence: 99%
“…1): the emulsification of a polymer solution containing the encapsulated substance, followed by particle hardening through solvent evaporation and polymer precipitation. During the water emulsification, the polymer in solution in the volatile, waterimmiscible solvent is broken into microdroplets by the shear stress produced by either a homogenizer or a sonicator in the presence of a surface-active agent until the polymer precipitates [24][25][26][27].…”
Section: Preparation Of Pei Dispersions By Emulsion/evaporationmentioning
confidence: 99%
“…These systems provide a pH-dependent drug release mechanism. [20][21][22] In drug microencapsulation, [23][24][25] the most used class of hydrophobic polymers is cellulose derivatives including ethyl cellulose (EC) and cellulose acetate butyrate (CAB) for a prolonged release. 26 Jelvehgari et al have shown that CAB formulations exhibit enough buoyancy to reside in the stomach over a prolonged and slower drug release.…”
Section: Introductionmentioning
confidence: 99%
“…41 The same remark was reported for other drug/EC microspheres preparations. 23,41 Considering the nature of the polymer matrix under the same process conditions, The CAB microspheres were smaller than the EC microspheres. Based on the particle sizes values, microspheres with a mean Sauter diameter of 166 µm with EC and of 113 µm with CAB were obtained.…”
mentioning
confidence: 99%
“…[9][10][11] Aliphatic polyester polymers degrade in to non-toxic monomers by bulk hydrolysis of the ester bonds, then avoiding the need for surgical removal so the risk of long term toxicity or a probable immunological reaction when compared with non degradable systems is also minimized. 12 Micro-encapsulation is a method of fabricating materials with valuable new properties in the pharmaceutical industry 13,14 and other fields; [15][16][17] it is one of the quality preservation techniques of sensitive substances. In current pharmacology, micro-encapsulation is employed as a masking technique and, in particular, to control and modify drug release.…”
Section: Introductionmentioning
confidence: 99%